An Evaluation of the Management of Majelis Taklim in Enhancing Islamic Brotherhood: A Case Study of Majelis Taklim Al-Huda - Zakiah Maulidi Putri; Iis Arifudin; Ria Yulia Gloria (MASI Mandiri Edukasi, 2026)
Majelis taklim plays an important role in social–religious guidance; however, much of the existing literature has focused on religious activities and spiritual development and has not examined in depth how management functions contribute to strengthening ukhuwah islamiyah (Islamic brotherhood). This study aims to evaluate Majelis Taklim Al-Huda’s efforts to reinforce ukhuwah islamiyah among its members by analyzing the implementation of core management functions. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis from September to November 2025, involving 10 informants (the head of the majelis, board members, the ustadzah, and active participants). The data were analyzed descriptively to map planning, organizing, implementation, and supervision practices and their implications for member cohesion. The findings indicate that management functions have not been implemented optimally. In planning, activities are conducted spontaneously, without written plans or needs assessments, leading to repetitive study themes. In organizing, management is ineffective due to unclear task distribution among board members and the absence of standard operating procedures (SOPs), both of which frequently hinder internal coordination. In practice, programs remain dominated by routine study sessions, with limited innovation in social or empowerment initiatives to increase participation. Meanwhile, the supervisory function is not systematically applied because activity reports and structured evaluation mechanisms are lacking. The study concludes that strengthening management through strategic planning, a clear organizational structure, program diversification, and regular evaluation is essential to improving the effectiveness of majelis taklim and reinforcing ukhuwah islamiyah. This research contributes by addressing the academic gap on the relationship between management functions and ukhuwah islamiyah, while enriching the literature on Islamic Education Management in the context of non-formal religious institutions.